'A splendid effort!' Print media reporting of England's women's performance in the 2009 Cricket World Cup. (February 2013) - Biscomb, Kay; Griggs, Gerald
The representation of female athletes by the British print media has been an area for close scrutiny since the mid-1990s. This article examines the representation of England's Women's performance at the 2009 Cricket World Cup. Using a qualitative content analysis of 29 articles from seven newspapers over the duration of the tournament, results show that the main themes emerging were: description of play, performance, celebration, media coverage and women's sport. These results are discussed in the context of changing trends since the 1990s. Concurring with previous authors we acknowledge that trends have changed in terms of what is reported but not in terms of how much is reported.